Neonatal hypoglycaemia in the offsprings of parents with maturity-onset diabetes of the young (MODY) - Maly, Jakub; Urbanova, Jana; Musil, Vladimir; Broz, Jan; Cerny, Milos; Brunerova, Ludmila (Journal of pediatric endocrinology & metabolism, 2025)
INTRODUCTION: Neonatal hypoglycaemia is the most common metabolic disorder of various causes, relatively rare being MODY (Maturity Onset Diabetes of the Young). CONTENT: Data search of relevant articles focused on hypoglycaemia in carriers of selected MODY gene mutations published from 2007 to 2022 was performed in databases Medline, PubMed, Cochrane and UptoDate based on key words: 'hyperinsulinemic hypoglycaemia', 'congenital hyperinsulinism', 'MODY', 'HNF4A mutation', 'HNF1A mutation'. SUMMARY: Loss of function of HNF4A and HNF1A genes comprises approximately to 5.9 % of diazoxide responsive hyperinsulinemic hypoglycaemia, which may appear in 15 % HNF4A mutation carriers. A typical finding of HNF4A mutation carriers with neonatal hypoglycaemia was a birth weight above 4000 g or above 97th percentile. OUTLOOK: Although mutations in MODY genes represent a rare cause of neonatal hypoglycaemia, they should be considered in the differential diagnosis, particularly in cases of persistent hypoglycaemia requiring intensive care.
Keywords: mutace; hepatocytární jaderný faktor 4; Diabetes Mellitus, Type 2; nemoci novorozenců; Parents; lidé; Infant, Newborn; hypoglykemie; hepatocytární jaderný faktor 1-alfa; Mutation; Hepatocyte Nuclear Factor 1-alpha; Infant, Newborn, Diseases; novorozenec; Hepatocyte Nuclear Factor 4; diabetes mellitus 2. typu; rodiče; Hypoglycemia; Humans